ISOLATION AND SCREENING OF ANTIBIOTIC PRODUCING ACTINOMYCETES FROM GARDEN SOIL OF SATHYABAMA UNIVERSITY, CHENNAI - KESAVAN S, SUDHA SRI; R, HEMALATHA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: To isolate and screen Actinomycetes with anti bacterial and antifungal activity from garden soil samples of Sathyabama University, Chennai. Methods: Six soil samples were collected, serially diluted and plated on starch casein agar supplemented with nalidixic acid and cyclohexamide for inhibition of bacteria and fungi, respectively. Primary screening of actinomycetes isolates was done by following cross streak method against test organisms. Submerged fermentation was followed for the production of crude antibiotics. Agar well diffusion method was done to determine the antimicrobial activity of the crude extract. The MIC also quantified for the crude extract by microtiter plate assay. The promising isolate was characterized by conventional methods. Results: On primary screening 13 out of 22 actinomycete isolates (59%) showed potential antimicrobial activity against one or more test bacteria and/or fungus. Â The isolate BN8 shows antagonistic activity against all the tested bacteria and fungi, isolates BN5 and BN16 were active against only bacteria not fungi, and Isolate BN2 was active against all tested fungi. The zone of inhibition was measured by using the crude extracts of all the four isolates. The crude extract produced by isolate BN8 showed zone on inhibition against all the tested bacterium in 100 Âµg/ml against Pseudomonas aeroginosa (22mm), Klebsiella pneumonia (25mm), Bacillus cereus (20mm), Staphylococcus aureus (22mm), Â Escherichia coli (15mm), Â Aspergillus flavus (14mm), Â Aspergillus niger (20mm), Â Â Aspergillus fumicatus (10mm) respectively. The crude extracts of isolates BN2, BN5, BN16 were not exhibited any zone of inhibition against the test microbes on agar well diffusion assay. The MIC of crude extract against Pseudomonas aeroginosa (50 Î¼g/ml), Staphylococcus aureus(25 Î¼g/ml), Klebsiella pneumonia (25 Î¼g/ml) and Bacillus cereus(25 Î¼g/ml) . The MIC value of the crude extract against the bacterium Escherichia coli was 12.5 Î¼g/ml. The MIC of 12.5 Î¼g/ml was observed in the crude extract against Aspergillus flavus, 25 Î¼g/ml against Aspergillus niger, and 50 Î¼g/ml against Aspergillus fumicatus respectively. Conclusion: This groundwork concluded that the soil samples of Sathyabama University have actinomycetes with metabolites inhibits bacterial and fungal pathogens. One of the promising isolate was identified which active against the test bacteria and fungi. The crude metabolite exhibits very large zone of inhibition when compared to the control antibiotic. The type of antimicrobial agents produced by the isolate and the phylogenic relationship of the isolate has to be investigated as well.